MicroRNA-regulated pathways of flow-stimulated angiogenesis and vascular remodeling in vivo - Henn, Dominic; Falkner, Florian; Thomas, Benjamin; Köpple, Christoph; Schulte, Matthias; Kneser, Ulrich; Schmidt, Volker-Jürgen (Journal of translational medicine, 2019)
Vascular shear stress promotes endothelial cell sprouting in vitro. The impact of hemodynamic forces on microRNA (miRNA) and gene expression within growing vascular networks in vivo, however, remain poorly investigated. Arteriovenous (AV) shunts are an established model for induction of neoangiogenesis in vivo and can serve as a tool for analysis of hemodynamic effects on miRNA and gene expression profiles over time.